2018
DOI: 10.1021/jacs.7b12444
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Self-Assembly Kinetics as a Route To Control the Morphology of Core-Crystalline Cylindrical Micelles

Abstract: Nucleated self-assembly in selective solvents of core-crystalline block copolymers (BCPs) is a special case of living supramolecular polymerization, leading to rodlike micelles of controlled and uniform length. For the crystallization-driven self-assembly of PFS-containing BCPs (PFS = polyferrocenyldimethylsilane), the formation of block comicelles by sequential addition of different BCPs is well-established. But there are only a few examples of living copolymerization, the simultaneous addition of pairs of BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 62 publications
(157 reference statements)
0
69
0
Order By: Relevance
“…This means that the value of Q in Equation varies with the length of the core‐forming block. Winnik and Manners also added two kinds of PFS‐containing BCPs into the solution of seed micelles and found that cylindrical comicelles with different structures could be formed, including block comicelles with different block lengths, comicelles composed of patchy block and single‐component blocks and gradient comicelles (Figure ). The formation mechanism of different comicelles originates from the different growth rates of the individual BCP unimers, like the different reactivity ratios of monomers in copolymerization.…”
Section: Kinetics For Epitaxial Growth Of Unimers Onto Seed Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the value of Q in Equation varies with the length of the core‐forming block. Winnik and Manners also added two kinds of PFS‐containing BCPs into the solution of seed micelles and found that cylindrical comicelles with different structures could be formed, including block comicelles with different block lengths, comicelles composed of patchy block and single‐component blocks and gradient comicelles (Figure ). The formation mechanism of different comicelles originates from the different growth rates of the individual BCP unimers, like the different reactivity ratios of monomers in copolymerization.…”
Section: Kinetics For Epitaxial Growth Of Unimers Onto Seed Micellesmentioning
confidence: 99%
“…Cylindrical comicelles with different structures formed by two poly(ferrocenyldimethylsilane) (PFS)‐containing block copolymers (BCPs) via seeded growth. Reproduced from Reference , with permission from American Chemical Society…”
Section: Kinetics For Epitaxial Growth Of Unimers Onto Seed Micellesmentioning
confidence: 99%
“…Interactions between crystalline portions, analogous to the ripening of crystal formation during micelle morphology transitions described previously, or the amorphous corona provides directed assembly pathways for new structures. Mixed coronas of co‐micelles were formed in a solution of PNIPAM‐ b ‐PFS and P2VP‐ b ‐PFS due to different growth kinetics of each block . Figure shows TEM images of CDSA cylinders with “patchy” coronas, where microphase separation created portions of the cylinder with one corona block, PNIPAM lighter portions, and sections with the other, darker P2VP (stained with Karstedt's catalyst).…”
Section: Conventional Crystallizable Diblock Copolymersmentioning
confidence: 99%
“…Below each image is a schematic representation of the assembly where yellow represents PFS, blue represents P2VP, and red represents PNIPAM. (Reproduced from with permission from the American Chemical Society)…”
Section: Conventional Crystallizable Diblock Copolymersmentioning
confidence: 99%
See 1 more Smart Citation